Awareness, attitude and accessibility of school adolescents to sexua l and reproductive health services in Wakiso district - Nabasiige, Teddy (Kampala, 2013)
Unpublished dissertation (M.ED. Sc. ) - Makerere University, 2013.
Includes bibliographical references.
Keywords: Adolescents -- Uganda -- Wakiso district; Sex instruction for teenagers; Preventive health services for teenagers -- Uganda -- Wakiso distric t